Study of phases of insulin secretion in pre-diabetes and newly diagnosed type 2 diabetes mellitus (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Insulin is released from the pancreas in a biphasic manner in response to arterial glucose concentration. The assumption has been generally made that the 30-minute response reflected first-phase insulin release, whereas the 120-minute response reflected second-phase insulin release.Objectives: The aim of this study was to identify the defect in first and second phases of insulin secretion in pre-diabetes and newly diagnosed T2DM.Methods: This case-control study was conducted in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from March 2013 to June 2014. All the study subjects (n = 94) were collected from the one point centre, BSMMU as newly diagnosed T2DM, pre-diabetes and healthy normal glucose tolerant subjects according to fasting plasma glucose and 2 hour plasma glucose status. A total of 32 newly diagnosed T2DM and 32 pre-diabetes were included on the basis of inclusion criteria as cases. Another 30 healthy normal glucose tolerant subjects were emolled as control. Fasting blood samples were collected from study subjects to estimate the plasma glucose and insulin level. Again blood samples were taken for measurement of plasma glucose and insulin level at 30 minute and 120 minute on OGTT.Results: Fasting plasma insulin was significantly higher in pre-diabetes than control and T2DM (p = 0.011). Plasma insulin at 30 minute and 120 minute of OGTT were significantly lower in T2DM than control and pre- diabetes (p = 0.001 & 0.016). The insulin secretion in first and second phases were significantly lower in T2DM patients than controls and pre-diabetes (p = 0.000). Beta-cell function was also significantly lower in T2DM than controls and pre-diabetes (p = 0.000). Median values of HOMA-IR were higher in pre-diabetes (1.68) and T2DM (1.53) than control (1.37), but not statistically significant (p = 0.153). There was significant positive correlation of both phases of insulin secretion with FPI, beta-cell function and insulin resistance in T2DM, pre-diabetes and controls.Conclusions: The study reveals that 1st and 2nd phase insulin secretory defect was detected in T2DM, but in pre-diabetes, we have failed to identify insulin secretory defects in both phases.